2017
DOI: 10.21037/atm.2017.04.34
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of quality of life after lung cancer resection

Abstract: Background: Surgical resection with curative-intent remains the gold standard for clinically operable early-stage non-small cell lung cancer (NSCLC). This goal can be accomplished using a minimally invasive option, e.g., video assisted thoracic surgery (VATS) or standard thoracotomy. Surgical techniques continue to evolve and few studies have compared the QOL of patients managed with these procedures using current approaches. The primary goal of this study was to investigate differences between patients manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Larger studies have explored HRQL after VATS but have been retrospective or crosssectional in design and do not measure HRQL pre-operatively. 8,9 Prospective studies measuring HRQL before and after VATS surgery have typically been small in size or used unvalidated or generic instruments that measure broad aspects of health, which may not adequately capture the complex and unique areas of function impaired by lung cancer 6,[10][11][12][13] or studied few patients. 11 Between 2008 and 2014, Bendixen and colleagues 14 questionnaire, a generic measure of health status; EORTC core quality of life questionnaire (QLQ-C30); pain rating scale] at baseline and at several time points for 12 months post-operatively.…”
Section: Graphic Abstractmentioning
confidence: 99%
“…Larger studies have explored HRQL after VATS but have been retrospective or crosssectional in design and do not measure HRQL pre-operatively. 8,9 Prospective studies measuring HRQL before and after VATS surgery have typically been small in size or used unvalidated or generic instruments that measure broad aspects of health, which may not adequately capture the complex and unique areas of function impaired by lung cancer 6,[10][11][12][13] or studied few patients. 11 Between 2008 and 2014, Bendixen and colleagues 14 questionnaire, a generic measure of health status; EORTC core quality of life questionnaire (QLQ-C30); pain rating scale] at baseline and at several time points for 12 months post-operatively.…”
Section: Graphic Abstractmentioning
confidence: 99%
“…For oncological surgery, resection status and survival rates seem to be more of clinical interest. However, more and more studies appeared focussing on quality of life after surgery, showing a decline during short-and long-term follow-up [28][29][30]. Different AEs, such as chronic pain, anxiety/depression or general mental function are increasingly moving into focus.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, their emotional, psychological, and physical scores were better than those in the malignant group. In their study on quality of life among patients with lung cancer, Hopkins et al [11] reported that patients had more pain and mood disorders in the first 6 months postoperatively. However, long-term quality of life was similar in patients who underwent VATS and those who had thoracotomy.…”
Section: Discussionmentioning
confidence: 99%